Novel method for feedstock production for high efficiency FZ c-Si PV. Issue 1 (9th March 2015) - Kravtsov, A
Abstract: The efficiency of solar cells manufactured from FZ wafers is significantly higher than the efficiency of cells made of CZ or multicrystalline wafers. The high cost of FZ silicon, however, limits the applicability of FZ wafers. The aim of the present work is to create a cost- effective method of FZ feedstock production based on pulling from skull with electron beam heating. This work covers the process of obtaining of raw silicon rods and FZ monocrystals from them.